The Effect of Managerial Ownership, Company Size, and Audit Committee on CSR Disclosure - Agistiani, Alfina; Nurfauziah, Farah Latifah; Latifah, Euis (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Corporate social responsibility is the responsibility to assess how much concern for the environment, the company must seriously and openly pay attention to the disclosure of social responsibility. This study aims to determine whether Managerial Ownership, Company Size and Audit Committee partially or simultaneously influence the Disclosure of Corporate Social Responsibility (CSR) in Food and Beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The data used in this study is secondary data and sample selection using purposive sampling. Based on the results of purposive sampling from 30 companies, 17 Food and Beverage companies met the sample criteria. The analytical method used is descriptive analysis, multiple linear analysis, and hypothesis testing. The results showed that managerial ownership had no partial effect on CSR disclosure based on the results of the t test, which had a coefficient value of 0.143 and a significant value of 0.132 >0.05. Company size had a negative effect on CSR disclosure with a coefficient value of -1.241 and a significant value of 0.000. 0.05.